Molecular determinants underlying functional innovations of TBP and their impact on transcription initiation - Charles N. J. Ravarani (Nature Portfolio, 2020)
The TATA-box binding protein (TBP) is required for transcription initiation in archaea and eukaryotes. Here the authors delineate how TBP’s function has evolved new functional features through context-dependent interactions with various protein partners.